ETIKA BIROKRASI PADA BADAN PEYELENGGARA JAMINAN SOSIAL (BPJS) DI KABUPATEN GOWA - Nasdir, Ananta Ilham; Rahim, Samsir; Riskasari, Riskasari (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2022)
ABSTRACTThe purpose of this study was to determine bureaucratic ethics in the administration of social security (BPJS) in Gowa Regency.  This type of qualitative descriptive research is to describe, describe and explain according to the problem of the results of research and objective history, qualitative methods are also referred to as artistic methods, because the research process is more artistic in nature and is referred to as interpretative methods and is very relevant to the research location taken.  The informants in this study amounted to 5 people. Based on the results of observations, interviews and documents, the research results are in accordance with the theory of Jay M. Shafritz (2012:99) which the author uses in looking at bureaucratic ethics at the Social Security Organizing Agency (BPJS) in Gowa Regency.  In the discussion of the results of this study will be described in accordance with the formulation of research problems that will be adapted to the theory of bureaucratic ethics according to Jay M. Shafritz.Keywords: Ethics, Bureaucracy, BPJS